Altered Cerebello‐Motor Network in Familial Cortical Myoclonic Tremor With Epilepsy Type 1. Issue 6 (4th March 2020) - Wang, Bo; Wang, Jue; Cen, Zhidong; Wei, Wei; Xie, Fei; Chen, You; Sun, Haiyang; Hu, Yunsong; Yang, Dehao; Lou, Yuting; Chen, Xinhui; Ouyang, Zhiyuan; et al.
Abstract: Background: Intronic pentanucleotide insertion in the sterile alpha motif domain‐containing 12 gene was recently identified as the genetic cause of familial cortical myoclonic tremor with epilepsy type 1. Objectives: We thereafter conducted a multimodal MRI research to further understand familial cortical myoclonic tremor with epilepsy type 1. Methods: We enrolled 31 patients carrying heterozygous pathogenic intronic pentanucleotide insertion in the sterile alpha motif domain‐containing 12 gene and 31 age‐ and sex‐matched healthy controls. We compared multimodal MRI metrics, including voxel‐based morphometry, fractional anisotropy of diffuse tensor imaging, frequency‐dependent percent amplitude fluctuation, and seed‐based functional connectivity of resting‐state functional MRI. Results: Significant decreased gray matter volume was found in the cerebellum. Percent amplitude fluctuation analysis showed significant interaction effect of "Frequency by Group" in three regions, including the vermis VIII, left cerebellar lobule VIII, and left precentral gyrus. Specifically, the lowest‐frequency band exhibited significant increased percent amplitude fluctuation in patients in the two cerebellar subregions, whereas the highest‐frequency band exhibited decreased percent amplitude fluctuation in the precentral gyrus in patients. Discriminative analysis by support vector machine showed a mean accuracy of 82% ( P = 1.0 –5 ). An increased functional connectivity between vermis VIII and the left precentral gyrus was found in patients with familial cortical myoclonic tremor with epilepsy type 1. A positive correlation between the percent amplitude fluctuation in the left cerebellar lobule VIII and duration of cortical tremor was also found. Conclusion: The cerebellum showed both structural and functional damages. The distinct change of spontaneous brain activity, that is, increased ultra‐low‐frequency amplitude in the cerebellum and the decreased higher‐frequency amplitude in the motor cortex, might be a pathophysiological feature of familial cortical myoclonic tremor with epilepsy type 1. © 2020 International Parkinson and Movement Disorder Society